Oral History Program Interview: Hattye Shields - Shields, Hattye
Born in 1926, between Checotah and Henryetta, Oklahoma, Shields grew up on farms. She gives a very detailed account of the trip to California, including dust storms and events along the way. She describes how her parents' felt demeaned when searched at the California border. Her family moved constantly between Oklahoma and California, stopping in Arvin and Wasco to work. She also remembers moving to follow the harvest seasons. This interview contains little on unions in the San Joaquin Valley, but Shields remembers her father working on a WPA project. She felt little prejudice as an "Okie."